The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-3024.2008.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Sm‐p80‐based DNA vaccine formulation induces potent protective immunity against Schistosoma mansoni

Abstract: SUMMARY Although there is an effective drug (praziquantel) available for the treatment of schistosomiasis, yet the disease is still spreading unabated and is rampant in 76 countries. Control via praziquantel treatment has so far been insufficient in reducing the disease transmission. Therefore a vaccine in addition to other strategies, for example, improving sanitation and introduction of new drugs are essential to successfully control and eventually eradicate schistosomiasis. To this effect we have targeted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 29 publications
9
87
0
Order By: Relevance
“…An effective anti-schistosome vaccine would contribute greatly to the decrease in morbidity associated with schistosomiasis via protective immune responses leading to reduced worm burdens and decreased egg production [510]. To this effect, high protective and antifecundity efficacy of Sm-p80 in both murine [1113] and nonhuman primate [14, 15] models clearly indicate that this antigen has a great potential as an important vaccine candidate for the reduction of morbidity associated with schistosome infection. Additionally, Sm-p80 was originally identified to be involved in the schistosome immune evasion process of surface membrane biogenesis [1619], thus Sm-p80 is an important functional protein and represents a unique target to invoke protective immunity against schistosome infection.…”
mentioning
confidence: 99%
“…An effective anti-schistosome vaccine would contribute greatly to the decrease in morbidity associated with schistosomiasis via protective immune responses leading to reduced worm burdens and decreased egg production [510]. To this effect, high protective and antifecundity efficacy of Sm-p80 in both murine [1113] and nonhuman primate [14, 15] models clearly indicate that this antigen has a great potential as an important vaccine candidate for the reduction of morbidity associated with schistosome infection. Additionally, Sm-p80 was originally identified to be involved in the schistosome immune evasion process of surface membrane biogenesis [1619], thus Sm-p80 is an important functional protein and represents a unique target to invoke protective immunity against schistosome infection.…”
mentioning
confidence: 99%
“…At present, to our knowledge, Sm-p80 is the sole schistosome vaccine candidate that has been tested for its prophylactic, antifecundity and therapeutic efficacy in different vaccine formulations and approaches (e.g., naked DNA alone; recombinant protein with adjuvants; and prime with DNA, followed by boosting with protein plus adjuvants) in two experimental animal models (mouse and baboon) of infection and disease. 16,[50][51][52][53][54][55][56][57][58][59][60][61][62] Furthermore, the validity of Sm-p80 as a viable vaccine candidate has been reinforced by the work of five "research groups" who have independently demonstrated reproducible and consistent protective efficacy in mice following challenge infection using calpain or its peptides as an antigen (Nagoya City University Medical School, Nagoya, Japan; 63 [50][51][52][53][54][55][56][57][58][59][60][61][62] ). Sm-p80-based vaccine formulations have three protective effects: worm reduction, antifecundity effect and protection against acute schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…and percent reduction of worm burden between control and vaccinated animals was calculated. 17,18,30 After the mice were sacrificed, liver and intestine samples were collected from each animal and digested in 4% KOH. The number of eggs present in the tissue was determined and percent reduction in egg production was calculated.…”
Section: Challenge Infection Necropsy and Estimation Of Worm And Eggmentioning
confidence: 99%
“…The number of eggs present in the tissue was determined and percent reduction in egg production was calculated. 17,18,30 Enzyme-linked immunosorbent assays Sera obtained following bleeding of all animals were pooled in their respective groups and ultimately used to determine antibody response. Briefly, 96-well microtiter plates were coated with 1.2 µg of recombinant Sm-p80 per well.…”
Section: Challenge Infection Necropsy and Estimation Of Worm And Eggmentioning
confidence: 99%
See 1 more Smart Citation